+ 2
Can anyone explain the logic for the following code in python
def sub(x,y): return x-y def mult(x,y): return x*y def pr(f1, f2, d): print(f1(f2(d+1, d), d)) pr(mult, sub, 4) answer is 4
2 Answers
+ 10
In this code
function pr(f1, f2, d) = pr(mult, sub, d)
f1 refer to mult function
f2 refer to sub function
d refer to 4
So for f2 : sub will be (x - y) = (d+1-d) = 1
So f2(d+1, d) = 1
Now print(f1(1, d))
So for f1 : mult will be (x*y) = 1*d = 1*4 = 4
so now f1(1, d) = f1(1, 4) = 4
now print(4) = 4
+ 5
look at line 6
first. subtraction 5 - 4 = 1.
then multiplication 1*4 = 4
then you print.